Acute Intoxication With Alcohol Reduces Trauma-Induced Proinflammatory Response and Barrier Breakdown in the Lung via the Wnt/β-Catenin Signaling Pathway - Noack, Laurens; Bundkirchen, Katrin; Xu, Baolin; Gylstorff, Severin; Zhou, Yuzhuo; Köhler, Kernt; Jantaree, Phatcharida; Neunaber, Claudia; Nowak, Aleksander J.; Relja, Borna (Frontiers in Immunology, 2022)
Background: Trauma is the third leading cause of mortality worldwide. Upon admission, up to 50% of traumatized patients are acutely intoxicated with alcohol, which might lead to aberrant immune responses. An excessive and uncontrolled inflammatory response to injury is associated with organ damage. We hypothesize, that along with inflammation-induced apoptosis, activation of Wnt/β-catenin signaling pathway causes breakdown of lung barrier and development of lung injury after trauma. It remains unclear whether ethanol intoxication (EI) prior trauma and hemorrhagic shock (HS) will attenuate inflammation and organ injury. Methods: 14 male C57BL/6J mice were randomly assigned to two groups and exposed either to EtOH or NaCl by an oral gavage, before receiving a femur fracture (Fx) and HS, followed by resuscitation (THFx). Fourteen sham animals received EtOH or NaCl and underwent surgical procedures without trauma. After 24 h oil red O staining of liver fatty vacuoles was performed. Histological lung injury score (LIS) was assessed to analyze trauma-induced lung injury. Gene expression of Cxcl1, Il-1b, Muc5ac, Tnf, Tnfrsf10b and CXCL1, IL-1b and TNF protein levels in lung tissue and bronchoalveolar lavage fluid were determined by RT-qPCR, ELISA, and immunohistological analyses. Infiltrating polymorphonuclear leukocytes (PMNL) were examined via immunostaining. Apoptosis was detected by activated caspase-3 expression in lung tissue. To confirm active Wnt signaling after trauma, gene expression of Wnt3a and its inhibitor sclerostin (Sost) was determined. Protein expression of A20 and RIPK4 as possible modulators of Wnt signaling pathway were analyzed via immunofluorescence. Results: Significant fatty changes confirmed acute EI. Histopathology and decreased Muc5ac expression revealed an increased lung barrier breakdown and concomitant lung injury after THFx versus sham. EI prior trauma decreased lung injury. THFx increased gene expression of pro-inflammatory markers but also pulmonary infiltration with PMNL and apoptosis versus sham, while EI prior THFx reduced those changes significantly. EI increased THFx-reduced gene expression of sost and reduced THFx-induced expression of wnt3a. While A20, RIPK4 and membranous b-catenin were significantly reduced after trauma, they were enhanced upon EI. Conclusion: These findings suggest that acute EI alleviates the uncontrolled inflammatory response and lung barrier breakdown after trauma by suppressing Wnt/β-catenin signaling pathway.